Persistent bias in advice-giving - Zhuoqiong Chen; Tobias Gesche (University of Zurich, Department of Economics, 2016)
We show that a one-off incentive to bias advice has a persistent effect on advisers' own actions and their future recommendations. In an experiment, advisers obtained information about a set of three differently risky investment options to advise less informed clients. The riskiest option was designed such that it is only preferred by risk-seeking individuals. When advisers are offered a bonus for recommending this option, half of them recommend it. In contrast, in a control group without the bonus only four percent recommend it. After the bonus was removed, its effect remained: In a second recommendation for the same options but without a bonus, those advisers who had previously faced it are almost six times more likely to recommend the riskiest option compared to the control group. A similar increase is found when advisers make the same choice for themselves. To explain our results we provide a theory based on advisers trying to uphold a positive self-image of being incorruptible. Maintaining a positive self-image then forces them to be consistent in the advice they give, even if it is biased.
Keywords: C91; D03; D83; G11; 330; advice-giving; conflict of interest; self-signaling; self-deception